Driving agricultural transformation with the power of information and communication technology: The performance of Nigeria’s growth enhancement support scheme - Olomola, Aderibigbe (International Food Policy Research Institute, 2015)
Nigeria liberalized input distribution and established the Growth Enhancement Support Scheme (GESS) in 2011 to deliver subsidized inputs to farmers as part of its Agricultural Transformation Agenda (ATA). Despite the relevance of the GESS as a subsidy delivery mechanism, its achievements during the first year of imple-mentation (2012) were below expectations. In 2015, as the first phase of the GESS is ending, has there been any significant improvement in its implementation? What improvements have occurred in redemption and par-ticipation rates? Even though the GESS is known to be making contributions in terms of ensuring direct access by farmers to subsidized inputs, the main determinants of farmers’ participation remain unknown. This study seeks to (i) examine the application of ICT innovations in the implementation of the GESS; (ii) assess its im-plementation performance from inception to date; and (iii) determine the factors influencing farmers’ participa-tion in the scheme. The study is timely and has significant policy relevance judging by the desire of the govern-ment of Nigeria to understand the performance of the GESS in view of the enormous financial and material resources that have been committed to the scheme since its inception in 2012. An evaluation of the perfor-mance of the GESS will provide the government with feedback required for making adjustments in input sub-sidy spending, especially in the face of the recently declining oil revenues. It becomes imperative to have evi-